Annual Plan 1999-2000 Volume I Schemewise Plan Outlay Government of National Capital Territory of Delhi - Planning Commission (Planning Commission, 1999)
The Annual Plan 1999-2000 is the third Annual Plan under the 9th Five Year Plan (1997-2002). Since this plan will eventually lead us into the next millennium, it is important that the Annual Plan 1999-2000 stands apart in some respect from the earlier two plans, by keeping in mind the Government of Delhi’s commitment that the Administration vis-a-vis planning has a "human face" Accordingly, a number of such schemes and programmes have been introduced in Annual Plan 1999-2000, which can be seen as a significant beginning in the new direction.
Planning Department, Government of National Capital Territory of Delhi